The effect of Nigella sativa and vitamin D3 supplementation on the clinical outcome in COVID-19 patients: A randomized controlled clinical trial - Said, Shimaa A.; Abdulbaset, Alsayyed; El-Kholy, Amal A.; Besckales, Osama; Sabri, Nagwa A. (Frontiers in Pharmacology, 2022)
Background: The coronavirus disease 2019 (COVID-19) is a novel coronavirus that causes severe infection in the respiratory system. Since the immune status plays an essential role in combating COVID-19, herbal medicines, which have an immunomodulatory effect, may help prevent and even treat COVID-19. Nigellasativa is one of the herbal medicines with antiviral and immunomodulatory activities, and its therapeutic effectiveness makes it a promising add-on therapy for COVID-19. In addition, vitamin D3 has an immunomodulatory role, but the effect of therapeutic vitamin D3 supplementation in SARS-CoV-2 infection is still not well-known. Objective: This study aims to investigate the effects of Nigella sativa and vitamin D3 as single supplemental therapies and in combination on viral clearance indicated by a negative polymerase chain reaction and the alleviation of symptoms during the study follow-up duration of 14 days. Patients and Methods: The study design was an open-label randomized controlled clinical trial conducted at the Respiratory Hospital at the Kobry El Qobba Armed Forces Medical Complex. In total, 120 COVID-19 patients with mild to moderate symptoms were randomly assigned to four groups, with thirty patients each, as follows: Group 1 received an oral dose of 900 mg Nigella sativa through 450 mg soft gelatin capsules twice daily for two weeks; Group 2 received 2,000 IU of vitamin D3 through 1000-IU tablets given as two tablets, once daily; Group 3 received 900 mg of Nigella sativa and 2,000 IU of vitamin D3 in the same manner of dosing as in the previous groups; and Group 4 was the control group. All groups received standard therapy for COVID-19 infections and clinical management of COVID-19’s clinical symptoms. Results: The Nigella sativa–vitamin D3 combination in addition to the standard therapy for COVID-19 infections significantly contributed to the alleviation of most COVID-19 symptoms: 50% of patients were free of cough after 7 days, 70% showed an absence of fatigue after 4 days, 80% had no headache after 5 days, 90% were free of rhinorrhea after 7 days, and 86.7% of the patients had no dyspnea after 7 days. Moreover, patients in the four studied groups showed a reduced median temperature after 3 days of treatment. Negative results of the polymerase chain reaction (PCR) test recorded on the 7th and 14th day of therapy were superior in the Nigella sativa and vitamin D3 combination arm compared to those of the other studied arms where the value of the odds ratio (OR) on the 7th day was 0.13 with 95% CI: 0.03–0.45 and that of the 14th day was 0.09 with 95% CI: 0.02–0.3. Conclusion: The results of this study showed a promising therapeutic benefit of the administration of Nigella sativa and vitamin D3 combination in COVID-19 patients with mild to moderate symptoms. Additionally, the remarkable viral clearance in a short time interval and reduction in the severity and progression of symptoms recommended the use of this combination as an add-on therapy for the management of COVID-19 patients. Clinical Trial Registration:ClinicalTrials.gov, Identifier: NCT04981743.